Atenção e memória visual na população idosa: uma associação etre as habilidades literárias sob condições de interferência. - Pedro Gabriel; Joseph Conboy (CAEN, 2010)
Deterioration in attention and memory is frequently observed in the elderly. Other factors, besides age, contribute to this deterioration, of course. In this study we describe an association between levels of formal education and deficits in attention and visual memory in the presence of interference. The participants (57 individuals between the ages of 65 and 92) responded to the Toulose-Piéron test and the Visual Reproduction sub-test of the Wechsler-R. The Stroop test was used to create interference conditions in the visual memory tasks. Independent of age, those seniors with more formal education performed better in the tests of concentration and on visual memory tasks in the presence of interference.